AaWRKY9 contributes to light- and jasmonate-mediated to regulate the biosynthesis of artemisinin in Artemisia annua - Fu, Xueqing (The New phytologist, 2021)
© 2021 The Authors. New Phytologist © 2021 New Phytologist Foundation.